Accurate description of calcium solvation in concentrated aqueous solutions - Kohagen, Miriam; Mason, Philip E; Jungwirth, Pavel (The journal of physical chemistry. B, 2014)
Calcium is one of the biologically most important ions; however, its accurate description by classical molecular dynamics simulations is complicated by strong electrostatic and polarization interactions with surroundings due to its divalent nature. Here, we explore the recently suggested approach for effectively accounting for polarization effects via ionic charge rescaling and develop a new and accurate parametrization of the calcium dication. Comparison to neutron scattering and viscosity measurements demonstrates that our model allows for an accurate description of concentrated aqueous calcium chloride solutions. The present model should find broad use in efficient and accurate modeling of calcium in aqueous environments, such as those encountered in biological and technological applications.
Keywords: vápník; radiační rozptyl; roztoky; neutrony; Calcium; Scattering, Radiation; Solutions; Viscosity; Neutrons; viskozita; Solubility; rozpustnost